Youth in the Society During the Pandemic. Subjective Evaluation of the Pandemic and Its Objective Consequences for Students in the Remote Teaching Process - Karol Leszczyński (The Francis de Sales Scientific Society (TNFS.PL), 2023)
The article discusses problems related to the educational crisis caused by the COVID-19 pandemic. The crisis hit the whole society, but it especially affected disadvantaged groups by increasing the existing social inequalities. The article, moreover, analyses factors influencing various ways of experiencing the pandemic and its effects by particular groups of students, as this age group was most severely affected by the pandemic. Contrary to adults, almost all students were transferred to the remote education for a prolonged period of time. This article presents first of all a subjective assessment of the period of remote education made by students, their understanding of the situation, how they assessed teachers, parents and their colleagues. Next, the article points to both the protective and risk factors related to experiencing crises, especially in the context of family and religiousness. Finally, the article illustrates how the pandemic deepened the existing social problems rather than created new ones, primarily affecting the most vulnerable groups.